Kejadian Toksoplasmosis pada Wanita Hamil Pemelihara Kucing dan Wanita Hamil Bukan Pemelihara Kucing di Puskesmas Tlogosari Wetan Kota Semarang - Dina Afrianti; Adita Puspitasari Swastya Putri; Wahyudi Wahyudi (Poltekkes Kemenkes Semarang, 2023)
Toxoplasma gondii (T. gondii) is a widespread zoonotic pathogen worldwide. This parasite grows inside the body of a cat as definitive host. Cats play an important role in the epidemiology of T. gondii because they are the only animal capable to shed oocysts which can withstand outside environment. Nowadays, transmission of T. gondii infection from cat to human increases in particular areas. This study aims to identify the incidence of toxoplasmosis in pregnant women Raise Cats and Not Raise Cats in Tlogosari Wetan Health Center Semarang City. This study was an descriptive observational research with case control design in two populations. Subjects are chosen based on certain criteria, This study was done to 25 respondents as pregnant women raise cats and 25 respondents who weren’t. The results obtained from serological analysis on 50 blood serum samples consisting of 25 blood serum samples of pregnant women raise cats with positive IgG antibody as many as 6 serum samples (24%) and 25 blood serum samples of pregnant women who are not raise cats obtained positive IgG antibody in 2 samples serum (8%). The total percentage of toxoplasmosis was 16% from 50 serum samples. It is necessary to carry out a large-scale serological survey to determine the prevalence of toxoplasmosis in pregnant women in Semarang City and necessary monitoring and treatment of pregnant women infected with Toxoplasma gondii.